2010
DOI: 10.1159/000318905
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Used for Intradermal Injections Is Incorporated into the Pericellular Matrix and Promotes Proliferation in Human Skin Fibroblasts in vitro

Abstract: Background: Over the past decade injectable hyaluronan (HA) formulations have been widely used to decrease the visibility of skin aging. However, little basic research has been performed to address their effect on dermal skin fibroblasts. Objective: The aim of the present study was to investigate whether human skin fibroblasts are affected by exogenous non-cross-linked HA with respect to proliferation, migration and extracellular matrix composition. Methods: The effect of a non-cross-linked HA on proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 87 publications
1
12
0
1
Order By: Relevance
“…1). This is particularly relevant in dynamic tissue environments, where sugar cell coats are involved in the regulation of a wide range of processes that involve cell rearrangements including cell migration (3)(4)(5), division (6), synaptogenesis (7), morphogenesis (8,9), cancer progression and metastasis (10)(11)(12). The aim of this study is to investigate the physical role that the hyaluronan sugar coat plays in mediating cell surface access.…”
Section: Introductionmentioning
confidence: 99%
“…1). This is particularly relevant in dynamic tissue environments, where sugar cell coats are involved in the regulation of a wide range of processes that involve cell rearrangements including cell migration (3)(4)(5), division (6), synaptogenesis (7), morphogenesis (8,9), cancer progression and metastasis (10)(11)(12). The aim of this study is to investigate the physical role that the hyaluronan sugar coat plays in mediating cell surface access.…”
Section: Introductionmentioning
confidence: 99%
“…According to several investigations, a monophasic, non-cross-linked HA with uniform particle size results in uniform spreading and defect augmentation compared to biphasic HA product [17]. On the other hand, Röck et al [18] reported excessive fibroblast proliferation induced by non-cross-linked HA formulation, and Wang et al [19] reported the de novo collagen production induced by cross-linked HA in photo-damaged human skin. These findings indicate that HA injection applied to humans might be useful for stimulating collagen production, which could achieve a longer augmentation effect.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that soluble HA facilitates assemble of a supramolecular pericellular structure [ 48 ] . Whether cross-linked HA has this property has not been established, nor whether injected stabilized HA can perform such functions.…”
Section: Applications Of Hyaluronan From Outside Skinmentioning
confidence: 92%